Manisnya Kopi di Era Liberal: Perkebunan Kopi Afdeling Malang, 1870-1930 - Rixvan Afgani; Sarkawi B. Husain (Diponegoro University, 2018)
This article discusses about the coffee plantation at Afdeling Malang in 1870-1930 with the dynamics of emergence on the agrarian laws during liberal period. This research uses historical method. It shows that the journey of coffee plantation during that time had been fluctuated. To achieve the expected production, foreign private investora were involved to establish new plantations or branch of the plantation (with the same brand). They did the nusery on coffee plants, the use of various types such as Robusta, Arabica/Java and Liberia. Towards 1898 until 1910s, bladziektedisease suffered coffee plants. The coffee production was decreased, it needed the another coffee variety that could more resist from disease. The malaisecrisis in 1930 had influenced coffee plantation, due to the number of coffee plantations were decrease, it affected the production that was lower compare than before.